DIGITAL ENGINEERING GEOLOGICAL MAP OF THE ATHENS PREFECTURE AREA AND RELATED DATABASE MANAGEMENT SYSTEM - Kynigalaki, M.; Nikolaou, N.; Karfakis, J.; Koutsouveli, An.; Poyiadji, El.; Pyrgiotis, L.; Konstantopoulou, G.; Bellas, M.; Apostolidis, Em.; Loupasakis, K.; Spanou, N.; Sabatakakis, N.; et al. (Bulletin of the Geological Society of Greece, 2010)
A digital engineering-geological map of the Athens Prefecture area was compiled at an original scale of 1:10.000 by IGME in cooperation with Engineering Geology Laboratory of Patras University. The map is related to a database management system constructed according to the project’s special needs, including geotechnical and geological data mainly obtained by boreholes and trial pits. The main map (11 sheets) is accompanied by three thematic maps at an original scale 1:50.000 (hydrogeological, tectonic) and 1:250.000 (seismic epicenters map). It constitute a basic tool for every activity of the Prefecture’s services, in relation to urban development, civil and environmental protection policy, sustainable management of natural resources, continual data supply to citizens and to the technical world. The main advantage of the digital map is the ability of constant updating of the related database, while this procedure should be established to serve social needs. As the mapping was based on a combination of conventional geological mapping techniques and the information from geotechnical database, it is considered to provide useful information for planners and decision makers at a preliminary planning level.